2017
DOI: 10.1101/193342
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

2D:4D and spatial abilities: From rats to humans

Abstract: Variance in spatial abilities are thought to be determined by in utero levels of testosterone and oestrogen, measurable in adults by the length ratio of the 2 nd and 4 th digit (2D:4D). We confirmed the relationship between 2D:4D and spatial performance using rats in two different tasks (pairedassociate task and watermaze) and replicated this in humans. We further clarified anatomical and functional brain correlates of the association between 2D:4D and spatial performance in humans.Many factors can influence p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…With a 2 × 2 full‐factorial mixed design we tested system‐wide consolidation processes of a spatial memory paradigm. During fMRI scans, participants engaged in allo‐ or egocentric spatial learning and memory retrieval in a previously validated human analogue of the water maze (Müller et al, 2018; Schoenfeld et al, 2017). Immediately before and after the learning and retrieval sessions, functional connectivity was assessed with resting‐state fMRI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With a 2 × 2 full‐factorial mixed design we tested system‐wide consolidation processes of a spatial memory paradigm. During fMRI scans, participants engaged in allo‐ or egocentric spatial learning and memory retrieval in a previously validated human analogue of the water maze (Müller et al, 2018; Schoenfeld et al, 2017). Immediately before and after the learning and retrieval sessions, functional connectivity was assessed with resting‐state fMRI.…”
Section: Methodsmentioning
confidence: 99%
“…Our study follows up on our investigations into the effect of sleep on allocentric and egocentric memory representations in humans and rats (Samanta et al, 2021). Participants performed a human analog of the watermaze (Morris, 1981), a validated paradigm to study different aspects of spatial navigation (Müller et al, 2018; Schoenfeld et al, 2017). Whereas Samanta et al (2021) focused on task‐fMRI data during learning and retrieval, here we focused on resting‐state fMRI and sleep‐EEG data.…”
Section: Introductionmentioning
confidence: 99%
“…Further, a human analogue of the maze has been developed and there is comparable performance in behavior across both species ( Schoenfeld et al. 2017 ; Müller et al. 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Only males were chosen since only male rats were used in the previous experiment. Additionally, sex differences studies across both rats and humans [20] have shown sex and menstrual cycle to influence sleep dependent memory consolidation and watermaze training. Participants were recruited through the Radboud Research Participation System.…”
Section: Methodsmentioning
confidence: 99%
“…We used the watermaze [16], which has been a well-established paradigm to study different aspects of spatial navigation, especially contrasting allo- and egocentric training [7, 17, 18]. Further, a human analog of the maze has been developed and showed comparable performance in behavior across both species [19, 20]. Using the watermaze we tested for the influence of sleep on allo- and egocentric spatial memory training in both rats and humans and investigated the underlying neural signatures with immediate early gene expression analysis in rats and functional MRI in humans.…”
Section: Introductionmentioning
confidence: 99%